STRENGTHENING THE LEGAL STATUS OF INVESTORS IN UZBEKISTAN THROUGH IMPROVING DISPUTE RESOLUTION MECHANISMS - Khayitmurodov Ulugbek Otabekovich (European Science Publishing, 2024)
The legal status of foreign investors plays an important role in the process of attracting and retaining foreign investments in the economy of any state. The article examines dispute resolution mechanisms relating to investors in the Republic of Uzbekistan, with an emphasis on arbitration and mediation of conflict resolution. Both international legal instruments and national legislative innovations aimed at improving the investment climate in the country are considered. The focus is on how strengthening dispute resolution mechanisms helps protect investors' rights and promotes their confidence in the Uzbek economy. The article also offers recommendations for improving national arbitration legislation taking into account international standards.
Keywords: legal status of investors, investment disputes, arbitration, mediation, investment climate, Uzbekistan, international law, investment protection.